Geosynthetic Clay Liner as Landfill’s Leachate Barrier - Budihardjo, Mochamad; Chegenizadeh, A; Nikraz, Hamid (Planetary Scientific Research Center, 2012)
Most of landfill sites in developed countries have used Geosynthetic clay liners (GCLs) as landfill leachate barriers to protect the environment. GCLs have some advantages in their shape, availability, easy in installation and mostly hydraulic performance. However, the GCLs also have some limitation for their resistance toward puncture, shear strength and bentonite loss in transport and handling. Duringtheir installation, more attention should be putting on to reduce the risk of GCLs’ damage that can compromise their performance. In this paper, a discussion of some advantages and disadvantages of GCLs as landfill liners will be presented to provide a clear understanding of GCLs.